INVESTIGAÇÃO SOROLÓGICA E MOLECULAR DE BARTONELLA SPP. E FATORES DE RISCO ASSOCIADOS EM DOADORES DE SANGUE NO MATO GROSSO DO SUL, BRASIL - Alanys Rafaela Bononi da Silva (2025)
Bartonella are Gram-negative, facultative intracellular bacteria that cause zoonotic diseases with clinical manifestations ranging from asymptomatic to potentially fatal. Transmission can occur through scratches or bites from infected animals, arthropod vectors, and blood transfusions. Therefore, this study aimed to estimate the seroprevalence and detect Bartonella spp. DNA in blood donors from Mato Grosso do Sul, Brazil. This is a descriptive, cross-sectional epidemiological study, approved by the Research Ethics Committee (CEP) of Fiocruz Brasília (Approval No. 5.746.612). Sample collection took place in May 2023 by convenience sampling. After obtaining informed consent, whole blood and serum samples were collected, along with the administration of sociodemographic and epidemiological questionnaires to blood donors at Hemosul. Seroprevalence was assessed using the Indirect Immunofluorescence Assay (IFA) with a commercial IgG anti-Bartonella henselae kit. The quality of DNA extracted from EDTA blood samples was evaluated by conventional PCR targeting the β-globin gene. Detection of Bartonella spp. DNA was performed using specific primers for the htrA, ITS, and ftsZ genes. Data analysis was conducted using Microsoft Excel and Epi Info software. PCR amplified products were subjected to Sanger sequencing. A total of 345 blood donor samples were analyzed. Among these, 17.10% (59/345) were reactive for IgG anti-B. henselae by IFA. All samples tested positive for the β-globin gene, confirming the quality of extracted DNA. No Bartonella spp. DNA was detected by the htrA and ITS genes; however, 5.22% (18/345) showed genomic DNA amplification using the ftsZ gene. Animal bites or scratches and being male were identified as risk factors associated with infection. BLAST analysis of the sequenced samples showed 100% identity with the ftsZ gene fragment of Bartonella henselae (BX897699.1), highlighting the potential risk of bacterial transmission, even in asymptomatic blood donors, and indicating the need for specific screening for Bartonella spp.